Etisk afgørende øjeblikke – en pragmatisk-dualistisk forskningsetik - Johansen, Martin Blok (Studier i Pædagogisk Filosofi, 2018)
This article analyses and discusses research-ethical dilemmas, ambivalences and problematic issues. This is done firstly by making a distinction between procedural research ethics and particularistic research ethics. Such a distinction refl ects a theoretical construction and generalization – in practice there can be a very close correlation between the two types. Hereafter, the distinction will therefore be used as a jumping-off point for the presentation of a pragmatic-dualist research ethics. Th e approach is dualist because it draws on the presence of two independent, contrasting understandings, which are essentially diff erent yet equal aspects of good research ethics; and it is pragmatic because this dualism is first and foremost structural and institutional by nature, and designed with an eye to what can realistically and expediently be done in practice. Thus the intention of the article is to both analyze and discuss two different understandings of research ethics and simultaneously qualify a research ethics that draws on both these understandings. At the same time, the intention is to try to visualize a diff erent understanding of research ethics which others can address and elaborate on or qualify but even at this point can be included in an arsenal or catalogue of research-ethical understandings and approaches that can be exploited in research-ethical practice.